2018
DOI: 10.1177/0022185617750418
|View full text |Cite
|
Sign up to set email alerts
|

The decline of Employers’ Associations in the UK, 1976–2014

Abstract: This article examines the collective, member-based Employers' Associations (EAs) in the UK that regulate the employment relationship by participating in collective bargaining. The main empirical contribution is to provide, for the first time, a longitudinal dataset of EAs in the UK.We use archival data from the UK Government's Certification Office to build a new dataset, identifying a decline of 81 per cent in the number of EAs between 1976 and 2013-2014. We also find that political agency and reducing levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 26 publications
(50 reference statements)
1
35
0
Order By: Relevance
“…Yet only 13 per cent of employers' associations take part in collective bargaining. 15 In a recent survey of the fortunes of UK unions over the last few decades, Jeremy Waddington identifies four structural elements in trade union decline. 16 First is longterm change in the composition of the UK labour market from manufacturing, which has tended to be highly unionised, to services, which is not.…”
Section: Reversing the Long Slow Decline Of Organised Labour?mentioning
confidence: 99%
“…Yet only 13 per cent of employers' associations take part in collective bargaining. 15 In a recent survey of the fortunes of UK unions over the last few decades, Jeremy Waddington identifies four structural elements in trade union decline. 16 First is longterm change in the composition of the UK labour market from manufacturing, which has tended to be highly unionised, to services, which is not.…”
Section: Reversing the Long Slow Decline Of Organised Labour?mentioning
confidence: 99%
“…Can the dual logics framework be applied to address our research question: what explains the changing role and activities of UK EOs? A recent study (Gooberman, Hauptmeier and Heery, 2019a) argued that the structure and activities of EOs have been transformed as a result of broader changes within the UK's system of employment relations. Given this change, we examine the pre-1979 pattern of EO representation and identify how the dual logics played out within this system.…”
Section: Reducing the Internal Power Of Members Ensures Greater Organmentioning
confidence: 99%
“…: Ibsen and Navrbjerg, 2018;Behrens and Helfen, 2016;Sheldon et. al, 2016;You and Barry, 2016;Zhu and Leyland, 2017;Gooberman, Hauptmeier and Heery, 2017, 2018, 2019a, 2019b demonstrated that employer collective organizations continue to thrive in countries featuring different institutional characteristics. These and other studies ensured that the 'strange non-death of employer and business associations' (Brandl and Lehr, 2016) emerged as a focus of study within employment relations.…”
Section: Introductionmentioning
confidence: 99%
“…The most noticeable change was the number of EOs bargaining collectively, declining from 418 in 1980 to 214 in 1997 and 97 in 2014. Although mergers helped total EO membership to stabilise in the 1980s, the collapse of national bargaining saw rapid decline thereafter, accentuated by structural decline in traditional manufacturing industries where bargaining was common (Gooberman, Hauptmeier, & Heery, ). The combined membership of EOs recorded by the Certification Office was 223,103 in 1980 and 204,072 in 1989, before declining to 146,813 by 1997 and 93,585 in 2014 .…”
Section: The Decline Of Collective Employment Relations and The Recasmentioning
confidence: 99%